Antimicrobial peptide LL‐37 attenuates infection of hepatitis C virus. Issue 9 (4th February 2016) - Matsumura, Takuya; Sugiyama, Nao; Murayama, Asako; Yamada, Norie; Shiina, Masaaki; Asabe, Shinichi; Wakita, Takaji; Imawari, Michio; Kato, Takanobu
Abstract : Aim: Although recent studies indicate that supplementation with vitamin D (VD) potentiates a sustained viral response by interferon‐based therapy to chronic hepatitis C, detailed mechanisms are not fully defined. The production of cathelicidin, an antimicrobial peptide, has been demonstrated to be part of the VD‐dependent antimicrobial pathway in innate immunity. Cathelicidin is known to directly kill or inhibit the growth of microbial pathogens including mycobacteria and viruses. Methods: We used a hepatitis C virus (HCV) cell culture system to clarify the anti‐HCV effects of the human cathelicidin, LL‐37. HuH‐7 cells were administrated with LL‐37 and infected with cell culture‐generated HCV (HCVcc). HCV propagation was estimated by measuring the level of HCV core antigen (Ag). Results: Treatment with LL‐37 resulted in decreased intra‐ and extracellular levels of HCV core Ag, suggesting inhibition of HCV propagation. To assess the effects of LL‐37 on HCV replication, JFH‐1 subgenomic replicon RNA‐transfected cells were treated with LL‐37. However, inhibition of HCV replication was not detected by this assay. To clarify the effects on HCV infection, we treated HCVcc with LL‐37 and removed the antimicrobial peptide prior to use of the virus in infection. This exposure of HCVcc to LL‐37 diminished the infectivity titers in a dose‐dependent fashion. Iodixanol density gradient analysis revealed that the peak fraction of infectivity titer was eliminated by LL‐37 treatment. Conclusion: The VD‐associated antimicrobial peptide LL‐37 attenuated the infectivity of HCV. This anti‐HCV effect of LL‐37 may explain the contribution of VD to the improved efficacy of interferon‐based therapy.